(untitled) (Applied Biological Research, 2015)
Studies were conducted to explore the possibility of using Azolla (Azolla pinnata) as feed ingredient in cow and broiler ration. In 1st study, 60 cross bred cows in their 2nd to 4th lactation were randomly divided into 2 groups and fed with or without Azolla supplemented commercial feed (1:1 :: Azolla: concentrate). Azolla-fed group showed a significant increase of 11.85% in milk production. In 2nd study, 220 one-day-old ‘Vencobb’ broiler chicks were divided into 2 groups and fed with commercial feed supplemented with or without dried Azolla meal [5% feed]. Result showed significant improvement in cumulative feed intake, body weight and FCR in broiler group fed with Azolla. The use of Azolla in cattle and broiler ration improved their production performance; so has a great potential as sustainable efficient feed supplement for cow and broiler (upto 5%).